Survey of Anaplasma Infections in Small Ruminants from East Part of Turkey - Altay, Kursat; Dumanli, Nazir; Aktas, Munir; Ozubek, Sezai (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
This study was carried out to determine the presence and frequency of Anaplasma ovis and Anaplasma phagocytophilum in small ruminants from Bingol, Elazig, Malatya and Mus provinces. A total of 422 (291 sheep and 131 goats) blood samples were collected from apparently healthy animals. To determine of A. ovis and A. phagocytophilum in small ruminants, species-specific PCRs were set up using 60 kDA chaperonin gene (cpn60, also known as hsp60 or groEL) and 16S SSU rRNA gene primer sets, respectively. A total of 301 (71.32%) animals were found infected with A. ovis and/or A. phagocytophilum. The percentages of positive animals for A. ovis and A. phagocytophilum were 67.06% (283/422) and 19.66% (83/422), respectively. The rate of concurrent infections was 15.40% (65/422). Four PCR products from positive samples were purified from agarose gel and sequenced. These sequences were identical to the reported nucleotide sequences of A. ovis and A. phagocytophilum. This is the first molecular based study on the detection of A. phagocytophylum and A. ovis in small ruminants from East Anatolia Region. Further studies are needed on the determination of the genotypes and vectors of the species.
Do?u anadolu bölgesinde koyun ve keçilerde anaplasma enfeksiyonlari{dotless}ni{dotless}n araşti{dotless}ri{dotless}lmasi{dotless}
Keywords: Anaplasma ovis; Anaplasma phagocytophilum; Sheep; Goat; East Anatolia Region